Giải phương trình: $\sqrt{x^{2}-9}$ +$\sqrt{x^{2}-6x+9}$ =0

Question

Giải phương trình:
$\sqrt{x^{2}-9}$ +$\sqrt{x^{2}-6x+9}$ =0

in progress 0
Adeline 1 năm 2021-07-05T17:41:36+00:00 2 Answers 40 views 0

Answers ( )

    0
    2021-07-05T17:42:36+00:00

    `\sqrt(x^2-9)+\sqrt(x^2-6x+9=0`

    `⇒\sqrt(x^2-9)=-\sqrt(x-3)^2`

    `⇒x^2-9=(x-3)^2`

    `⇒x^2-9=x^2-6x+9`

    `⇒6x=18`

    `⇒x=3`

    Vậy `x=3`

    0
    2021-07-05T17:42:59+00:00

    ` \sqrt{x^2 – 9} + \sqrt{x^2 – 6x + 9} = 0 `

    ` <=> \sqrt{x^2 – 9} = -\sqrt{x^2 – 6x + 9} `

    ` <=> x^2 – 9 = x^2 – 6x + 9 `

    ` <=> -6x + 9 = -9 `

    ` <=> -6x = -18 `

    ` <=> x = 3 `

    Vậy ` S = {3} `

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )